2014
DOI: 10.3390/s140508235
|View full text |Cite|
|
Sign up to set email alerts
|

Design, Development and Testing of a Low-Cost sEMG System and Its Use in Recording Muscle Activity in Human Gait

Abstract: Surface electromyography (sEMG) is an important measurement technique used in biomechanical, rehabilitation and sport environments. In this article the design, development and testing of a low-cost wearable sEMG system are described. The hardware architecture consists of a two-cascade small-sized bioamplifier with a total gain of 2,000 and band-pass of 3 to 500 Hz. The sampling frequency of the system is 1,000 Hz. Since real measured EMG signals are usually corrupted by various types of noises (motion artifact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…This research demonstrated that SEMG can accurately reflect the state of neuromuscular function in patients. SEMG has also been used for the evaluation of muscle function in patients with LDH [23][24][25][26]. Preliminary studies showed that the evaluation of muscle function using both frequency and time domains was more specific and objective than the simple biomechanical method [27].…”
Section: Discussionmentioning
confidence: 99%
“…This research demonstrated that SEMG can accurately reflect the state of neuromuscular function in patients. SEMG has also been used for the evaluation of muscle function in patients with LDH [23][24][25][26]. Preliminary studies showed that the evaluation of muscle function using both frequency and time domains was more specific and objective than the simple biomechanical method [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many researches related to measurement of walking and running have been reported to analyze human gait [1][2][3][4][5][6]. In these researches, it is important to measure the Ground Reaction Force (GRF) because the GRF is the only external force acting on human during walking or running except for the gravity [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there exist a number of various types of techniques for noise reduction. Among these techniques, the wavelet based de-noising method has been considered as one of the most efficient techniques [1]. Since decades ago, wavelet-based techniques have been extensively used in digital signal processing [2] [3].…”
Section: Introductionmentioning
confidence: 99%